Creep And Isothermal Fatigue Behaviour Of Eutectic SnPb, SnBi And SnZn Solders For Microelectronic Packaging At Mildly Elevated Temperatures - Hashim, Md. Amin (2011)
Interconnect materials are used to connect surface mounting components and other passive and discrete circuit components on to copper pads or lands, and in holes on the printed circuit boards. Presently, the industrial practice is using thermal cycling as a method for reliability testing of circuit boards with assembled components. Bulk specimens of 63Sn37Pn solder alloy were subjected to isothermal fatigue at three mildly elevated temperatures (30, 40 and 50oC), loading frequencies (6, 60 and 600 CPM) and at different applied peak stresses (ranging from 8.75 to 33.25 MPa).